Effects of the cooperative exporters of coffee in the growth of the solidarity economy in Colombia - Vargas Prieto, Amanda; Castañeda Guzmán, Diana Carolina (REVESCO. Revista de Estudios Cooperativos, 2019)
The objective of this article is to identify the effect generated by coffee exporting cooperatives in the growth of the solidarity sector in Colombia. Through a qualitative methodology it is shown that coffee exporting cooperatives have a positive effect on the growth of the solidarity sector, and are representative of it, since they are a driving force for the agricultural sector, besides being a fundamental player in International trade, and social development investment, through the investment of formal education, and other agricultural education programs, through which the good use of the cooperative model is encouraged.
Keywords: Cooperatives; Coffee cooperatives; Solidarity economy; Colombia; Exports.